THE ROLE OF RISK-TAKING AND ESG ON FIRM VALUE: EVIDENCE FROM INDONESIA FOR THE PERIOD OF 2014-2020 - Evita Sonny; Arief Wibisono Lubis (Jurnal Scientia, 2023)
To maximize shareholder wealth, management must strive to increase the firm value. Thus, this study aims to investigate the impact of risk-taking and ESG on firm value. The result of this research will explain whether the firm value as measured by Tobin's Q can be influenced by the level of risk-taking. In addition, this study also explores whether ESG affects firm value, and whether ESG can be used as a moderating variable in risk-taking and firm value relationships. The study period covered 2014 through 2020, and the research sample included 30 companies listed on the Indonesia Stock Exchange (IDX). Banking companies were excluded from the research sample due to differences in business models and levels of regulation. We use a fixed effect model of panel data regression in data processing, equipped with robust standard error. The first finding establishes that excessive risk-taking behavior exists at the managerial level, and it has a significant negative impact on firm value. Then, the second finding results in a significant negative effect of ESG on firm value, explaining ESG as a burdensome commitment to the firm value. Lastly, the final finding demonstrates that ESG does not significantly moderate the relationship between risk-taking and firm value. These findings are justified by the poor quality and insufficient transparency of ESG in Indonesian companies that have failed to limit excessive risk-taking in corporate management.